Listeria monocytogenes Response to Sublethal Chlorine Induced Oxidative Stress on Homologous and Heterologous Stress Adaptation - Bansal, Mohit; Nannapaneni, Ramakrishna; Sharma, Chander S.; Kiess, Aaron (Frontiers in Microbiology, 2018)
The objective of this study was to determine the effect of chlorine induced sublethal oxidative stress against homologous and heterologous stress adaptations in five Listeria monocytogenes (Lm) strains. Lm cells were exposed to gradually increasing sublethal concentrations of total chlorine/day: 250 ppm (day 1), 270 ppm (day 2), 290 ppm (day 3), 310 ppm (day 4), 330 ppm (day 5), 350 ppm (day 6) and 375 ppm (day 7) in tryptic soy broth (TSB). Changes in minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of Lm cells exposed to chlorine and control (non-adapted cells) were determined by the macro-dilution method. Chlorine-adapted Lm cells were also evaluated for changes in antibiotic resistance using the Kirby-Bauer disk diffusion and MIC double dilution assay as per the Clinical and Laboratory Standards Institute (CLSI, 2016) guidelines. In four Lm strains (Scott A, V7, FSL-N1-227 and FSL-F6-154) after adapted to sublethal chlorine, the MIC (600 ppm) and MBC (700 ppm) values of chlorine were slightly higher as compared to control (500 ppm MIC, and 600 ppm MBC). The Kirby-Bauer and MIC double dilution assays showed some significant changes in antibiotic susceptibility patterns for antibiotics such as streptomycin, gentamicin and ceftriaxone (p < 0.05). However, the changes in zones of inhibition and MIC values to all antibiotics tested for the chlorine-adapted and non-adapted (control) Lm cells were still within the susceptible range. Transmission electron microscopy studies showed that changes in cell wall and membrane integrity resulting, from the elongation of cells, may contribute to the possible routes of its increase in tolerance to chlorine and selective antibiotics. These findings indicate that the continuous exposure of Lm cells to chlorine may lead to significant changes in homologues and heterologous stress adaptation.